Kajian Teori Psikologis Fenomena Madonna-Whore Complex Dalam Buku Cantik Itu Luka Karya Eka Kurniawan - Imta Kayeki; Najwa Salsa Bila Wijaya; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the phenomenon of the Madonna Whore Complex in the beautiful book Luka. The Madonna Whore Complex is a psychological theory proposed by the father of psychology, Sigmund Freud. In this theory, humanitas are separated into two kinds, namely, madonna, which means holy, love, and asexual. While whore, which means sexual, lust, and broken, People with this complex compartmentalize their partners into two camps: those who are considered to be lustful and life partners. This is due to the split between the flow of affection and the sexual flow in male desire. This phenomenon makes a person unable to see his partner sexually. The issues raised in the beautiful book Luka are about prostitution, feminism, and gender inequality. The method used in this study is to use qualitative methods that are expected to be able to determine the values contained in the beautiful book based on The Theory of Madonna Whore Complex by Sigmund Freud. This study shows the results of the analysis of intrinsic elements through sexual behavior contained in the beautiful book Luka related to the Madonna Whore Complex theory proposed by Sigmund Freud.